STRATEGI PENGEMBANGAN BALAI PENELITIAN BIOTEKNOLOGI PERKEBUNAN INDONESIA - Muhammad Fauzanul Hakim Abdurrahim; Arief Daryanto; Rita Nurmalina (Jurnal Manajemen & Agribisnis, 2014)
The purpose of this study were to identify and review external and internal factors influencing Balai Penelitian Bioteknologi Perkebunan Indonesia (BPBPI) in achieving its vision and mission, to set up alternative development strategies in BPBPI and to formulate priority strategies for development of BPBPI. Descriptive analysis method were used in this study is. The analysis tools being used in this study were environmental analysis, internal factor evaluation, external factor evaluation, internal external matrix (IE), strengths weaknesses opportunities threats (SWOT) and combination of analytical hierarchy process (AHP) and SWOT. Using IE Matrix, the company were indicated to be in the position of Quadrant V, which is ‘hold and maintain’ position with general strategy is market penetration and product development. Based on the results of SWOT analysis, were identified six alternative strategies that can be recommended in the development BPBPI is (1) Market penetration strategy through development new products and improved distribution network, (2) Finding an alternative sources of new organic raw materials and cheap as well has a lots availability, (3) Improvement on BPBPI’s products promotional strategy through road show to consumers in periodical, (4) Strategy optimization experimental farm through planting excellence seeds, (5) Conducting strategic research to generating unique products and has a high value selling as well broad market, (6) Improve welfare expert for the creation of conducive working atmosphere. Priority strategy with highest total efficiency values (18,15%) obtained from AWOT were conducting strategic research to generating unique products and has a high value selling as well broad market.Keywords: development strategy, BPBPI, AWOT, SWOTABSTRAKTujuan dari penelitian ini adalah menentukan faktor-faktor internal dan eksternal yang Memengaruhi BPBPI dalam mencapai visi dan misinya, menyusun alternatif strategi pengembangan di BPBPI, dan merumuskan prioritas strategi pengembangan di BPBPI. Metode analisis deskriptif digunakan dalam penelitian. Alat analisis yang digunakan dalam penelitian ini adalah analisis lingkungan, efaluasi faktor internal, efaluasi faktor internal, matrik internal eksternal (IE), matrik SWOT dan kombinasi dari analisis proses Hierarki (AHP) dan SWOT. Menggunakan matrik IE, perusahaan diindikasikan berada pada posisi kuadran V yaitu posisi jaga dan pertahankan dengan strategi umum penetrasi pasar dan pengembangan produk. berdasarkan hasi analisis SWOT, terdapat enam alternativ strategi yang dapat direkomendasikan kepada BPBPI yaitu (1) Strategi penetrasi pasar melalui pengembangan produk-produk baru dan peningkatan jaringan distribusi, (2) Mencari alternatif sumber bahan baku organik yang baru dan murah serta memiliki ketersediaan banyak, (3) Strategi peningkatan promosi produk BPBPI melalui roadshow ke konsumen secara berkala, (4) Strategi optimalisasi kebun percobaan melalui penanaman bibit unggul, (5) Melakukan riset-riset strategis yang menghasilkan produk-produk unik dan mempunyai nilai jual tinggi serta pasar yang luas, (6) Strategi Peningkatan kesejahteraan tenaga ahli agar terciptanya suasana kerja yang kondusif. Prioritas strategi dengan total nilai efisiensi tertinggi (18,15%) yang diperoleh dari AWOT yaitu melakukan riset-riset strategis yang menghasilkan produk-produk unik dan mempunyai nilai jual tinggi serta pasar yang luas.Kata Kunci: strategi pengembangan, BPBPI, AWOT, SWOT